Metal Hydride‐Based Hydrogen Storage Tank Coupled with an Urban Concept Fuel Cell Vehicle: Off Board Tests. (7th May 2018) - Capurso, Giovanni; Schiavo, Benedetto; Jepsen, Julian; Lozano, Gustavo A.; Metz, Oliver; Klassen, Thomas; Dornheim, Martin
Abstract: In this work, the tests of a hydrogen storage system intended for vehicular applications, using a metal hydride as storage material, are reported. The system is designed to deliver gas to a fuel cell prototype vehicle. The room temperature hydride is an interstitial alloy, which is selected for its capacity to absorb and desorb hydrogen over an appropriate range of temperature and pressure. The static tests aim to assess whether the requirements for hydrogen release are reliably met by the tank setup. Hypothetical on‐road tests have been designed and applied. Dynamic tests allow moving from energy to power density. Solutions are adopted to face the issues of thermal management at higher‐demanding performances. Several cycles have been performed to find the ideal settings to preserve high average and peak gas flow in a realistic situation. The use of a metal hydride, to replace pressurized gas, results in improved performances, including an extended range at lower loading pressures. Decreasing the pressure in the storage system enables the advantageous possibility to reload the tank several times with commercially available cylinders. Possible future enhancements in the reduction of the total weight of the system are also considered. Abstract : In this study, it is shown that a metal hydride‐based hydrogen storage tank can be successfully used in a prototypical vehicular application . The metal hydride can store and deliver hydrogen in an appropriate range of temperature and pressure, and its energy density is comparable to gaseous H2 storage and common commercial batteries.